Accuracy of frozen section diagnosis and factors associated with final pathological diagnosis upgrade of mucinous ovarian tumors - Park, Jeong-Yeol; Lee, Sang-Hun; Kim, Kyu-Rae; Kim, Young-Tak; Nam, Joo-Hyun (Journal of gynecologic oncology, 2019)
To determine the accuracy of frozen section diagnosis and factors associated with final pathological diagnosis upgrade in patients with mucinous ovarian tumors. This study included 1,032 patients with mucinous ovarian tumors who underwent frozen section diagnosis during surgery. Sensitivity, specificity, and diagnostic accuracy of frozen section diagnosis was calculated. Univariate and multivariate regression analyses were performed to determine factors associated with diagnosis upgrade in the final pathology report. The sensitivity and specificity of frozen section diagnosis were 99.1% (95% confidence interval [CI]=98%-99.6%) and 82.2% (95% CI=77.9%-85.7%), respectively, for benign mucinous tumors; 74.6% (95% CI=69.1%-79.4%) and 96.7% (95% CI=95.2%-97.8%), respectively, for mucinous borderline ovarian tumors; and 72.5% (95% CI=62.9%-80.3%) and 98.8% (95% CI=97.9%-99.3%), respectively, for invasive mucinous carcinomas. The multivariate analysis revealed that mixed tumor histology (odds ratio [OR]=2.8; 95% CI=1.3-6.3; p=0.012), tumor size >12 cm (OR=2.5; 95% CI=1.5-4.3; p=0.001), multilocular tumor (OR=2.9; 95% CI=1.4-6.0; p=0.006), and presence of a solid component in the tumor (OR=3.1; 95% CI=1.8-5.1; p<0.001) were independent risk factors for final pathological diagnosis upgrade. Mixed tumor histology, tumor size >12 cm, multilocular tumor, and presence of a solid component in the tumor were independent risk factors for final pathological diagnosis upgrade based on frozen section diagnosis.